Higher circulating adiponectin and lower orosomucoid were associated with postload glucose ≤70 mg/dL, a possible inverse marker for dysglycemia, in young Japanese women - Satomi Minato; Kaori Kitaoka; Mika Takeuchi; Ayaka Tsuboi; Miki Kurata; Tsutomu Kazumi; Keisuke Fukuo; Megumu Yano; Gen Yoshino; Bin Wu (BMJ Open Diabetes Research & Care)
Objective To examine whether serum adiponectin and orosomucoid were associated with postload glucose ≤70 mg/dL during an oral glucose tolerance test (OGTT), termed as postload low glycemia, a possible inverse marker for dysglycemia.Research design and methods 75 g OGTTs were performed with multiple postload glucose and insulin measurements over a 30–120 min period in 168 normal-weight Japanese women (18–24 years). Insulin resistance (IR) and β-cell function inferred from serum insulin kinetics during OGTT, fat mass and distribution by dual-energy X-ray absorptiometry (DXA), serum adiponectin and inflammatory markers were compared cross-sectionally between 39 women with and 129 women without postload low glycemia.Results Of 168 women, 161 had normal glucose tolerance. Women with as compared with those without postload low glycemia had lower fasting and postload glycemia despite similar fasting and postload insulinemia. They had higher insulinogenic index (p=0.03) and lower adipose IR (a product of fasting free fatty acid and insulin, p=0.01), although DXA-derived general and central adiposity, the Matsuda Index and homeostasis model assessment-IR did not differ. In addition, they had higher adiponectin and lower orosomucoid (both p<0.001). Multivariate logistic regression analyses revealed that adiponectin (OR: 1.14, 95% CI 1.03 to 1.26, p=0.009) and orosomucoid (0.96, 0.93 to 0.97, p=0.008) were associated with postload low glycemia independently of adipose IR and insulinogenic index.Conclusions Higher adiponectin and lower orosomucoid were associated with 70 or lower mg/dL of postload glucose, a possible inverse marker for dysglycemia, in young women independently of DXA-derived fat mass and distribution, insulin secretion and IR.